Reviewing the Prosecution of Medical Practitioners in Common Law Countries: A Needed Step or a Flawed Approach? - Wahab, Mohd. Iqbal Bin Abdul; Qazi Zada, Mohd Ziaolhaq (Universitas Muhammadiyah Yogyakarta, 2019)
The prosecution of medical practitioners for the medical gross negligence has dramatically increased in the past decades. This was in a bid to curb the high prevalence and occurrence medical malpractice by the medical community. However, there are no proper data to support that the prosecution had any significant impact in reduction of such occurrences. Many believe that the criminal prosecution for medical practitioners in the course of their duties is not a right approach to take on. This paper aims to examine the medical gross negligence that occurred by the medical practitioners by reference to the various different common law countries and decided cases.Â